PENERAPAN MODEL CHALLENGE BASED LEARNING DENGAN METODE EKSPERIMEN DAN PROYEK DITINJAU DARI KEINGINTAHUAN DAN SIKAP ILMIAH TERHADAP PRESTASI BELAJAR SISWA - ., Sodikin (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The purposes of the research were to know the effect of challenge based learning (CBL) model by experiments method and project, learning of inquiring and scientific attitude and their interaction towards studentsâÂ achievement in cognitive, affective and psychomotoric. Data was collected using test technique for cognitive, non test technique for affective, psikomotoric, learning motivation, learning activity, and obsevation sheet is used for affective and psychomotoric. The data were analyzed by using anova test through software PASW 18.Â Based on the analysis of the data concluded: 1) there was effect of CBL model by experiments method and project toward cognitive, affective and psychomotoric towards studentsâ achievement; 2) there was an effect of learning inquiring towards cognitive and affective studentsâ achievement, but there was no effect towards psychomotoric studentsâ achievement; 3) there was an effect of scientific attitude toward cognitive studentsâ achievement, but there was no effect toward affective and psychomotoric studentsâ achievement; 4) there was no an interaction between CBL model by experiments method and project method with learning inquiring toward cognitive, affective and psikomotoric studentâ achievement; 5) there was no an interaction between CBL model by experiments method and project method with scientific attitude toward cognitive, affective and psychomotoric studentsâ achievement; 6) there was no an interaction between learning inquiring with scientific attitude toward cognitive, affective and psychomotoric studentsâ achievement;Â 7) there was no an interaction between CBL Â model by experiments method and project with learning inquiring and scientific attitude toward cognitive, affective and psychomotoric studentsâ achievement.